Inhibitor development in correlation to factor VIII genotypes - El Maarri, O. (2002)
Alloantibodies (inhibitors) against factor VIII (FVIII) develop in 20–30% of patients with severe haemophilia A and render classical FVIII substitution therapy ineffective. Several studies have shown that genetic factors, the type of FVIII gene mutation and immune response genes (e.g. the Major Histocompatibility Complexes), influence the risk of inhibitor formation. In particular, the type of FVIII gene mutation has proven to be a decisive risk factor. Patients with severe molecular gene defects (e.g. large deletions, nonsense mutations, intron-22 inversion) and no endogenous FVIII synthesis have a 7–10 times higher inhibitor prevalence than patients with milder molecular gene defects (e.g. missense mutations, small deletions, splice site mutations). To date, at least 10 distinct classes of mutations have been shown which have differing risks of associated inhibitor formation. A challenging observation in inhibitor patients is the heterogeneity of the antibody epitopes with respect to their number and their specifity. At least five epitopes in the FVIII molecule have been identified that constitute the targets for antibodies in most inhibitor patients. These epitopes are located in the ar3 region and the A2, A3, C1, C2 domains which correspond to the functional binding sites of the ligands of the FVIII protein. At present, the determinants of the characteristics of these epitopes and the subsequent inhibitor titre are unknown. A relationship of the mutation site and the epitope localization has been shown for some individual patients with mild haemophilia A. However, in severely affected haemophilia A patients, the influence of patient genetics on inhibitor titre and epitope specifity has yet to be elucidated.